Analisis Potensi Ekowisata Bahari di Pulau Larea-Rea Kabupaten Sinjai - Wahyuni, Ayu; Subariyanto, Subariyanto; Rahmah, Nur (Politeknik Negeri Sambas, 2023)
Each region has a different potential depending on its natural resources. Therefore, a separate study is needed to determine its potential; for example, it's potential for marine ecotourism. This study aims to determine potential strategies for developing marine ecotourism on Larea-Rea Island. This study used a descriptive qualitative method. The data collection techniques included observations and structured interviews. Data were analyzed using SWOT analysis by looking at the potential of using the Strengths, Weaknesses, Opportunities, and Threats found on Larea-Rea Island. The results of this study show that Larea-Rea Island has the potential to develop into a marine ecotourism area. The results of the SWOT analysis show that there are four alternative appropriate management strategies for building marine ecotourism on Larea-Rea Island:1) maximizing the promotion of marine tourism on Larea-Rea Island, 2) improving roads to tourist sites, 3) repairing and equipping facilities and infrastructure for tourism activities, and 4) conducting community development to become tour guides and tourism insights, and the importance of maintaining tourist sites.